3-D body-wave tomography from the seismic ambient noise recorded by a dense array in the Dehdasht area, Iran. Issue 2 (27th March 2023) - Riahi, Ali; Shomali, Zaher-Hossein; Obermann, Anne; Kamayestani, Ahmad
SUMMARY: The strong attenuation of the thick sedimentary layers in the Dehdasht region, Iran, renders active seismic exploration surveys difficult. The imaging of the existent limestone reservoirs is limited to the shallow subsurface due to the strong attenuation of seismic waves. Here, we discuss a different approach to imaging the subsurface using body waves extracted from the cross-correlation of the seismic ambient wavefield. We discuss the technical challenges to extracting clear P -wave arrivals from the seismic ambient wavefield of a dense 3-component seismic array deployed in the Dehdasht basin. We invert the data for the 3-D P -wave velocity structure and compare the velocity model with results from the 2-D active seismic surveys in the area. The results show the potential of using body waves extracted from the seismic ambient wavefield for imaging purposes in highly attenuating areas.